The value of environmental (dis)amenities in the urban housing market: Evidence from Khulna, Bangladesh - Md. Sariful Islam; Ruqaiya Hossain; Md. Manjur Morshed; Sonia Afrin (Journal of Urban Management, 2020)
Pressure of rapid urbanization on abiotic environmental parameters in the residential blocks is one of the major challenges of city corporation authorities in Bangladesh. Environmental degradation often reduces property value in the housing market. However, the studies attempted to assess the value of environmental amenities and dis-amenities in the housing market of Bangladesh are scarce. Hence, this study examines the economic value of environmental (dis)amenities in the housing market of Khulna city, Bangladesh. Hedonic pricing method was used to assess the value of four environmental attributes - ventilation, open space, waterlogging and landfill by waste in the housing market. The study found these environmental attributes explain the variation of house rents significantly. Environmental amenities - a hundred-meter reduction in proximity to open space leads to a 2 percent increase in rent while a one discrete unit increase in a 5-point ventilation improvement scale from very poor to excellent results in 5.4 rent increase - are found as rent booster in the urban housing market. In contrast, waterlogging and landfill by waste reduce house rents by 3.7 and 9.8 percent for one unit increase in the respective 5-point degradation scales. The further analysis showed that the rental price of planned residential areas is more sensitive to ventilation and landfilling while that of unplanned areas is more sensitive to both environmental dis-amenities - water-logging and landfilling. Furthermore, our study computed the implicit price of these environmental (dis)amenities in the housing markets of Khulna city. This study suggests improving environmental quality boosts house rent, which in turn attracts environment-friendly urbanization.
Keywords: R21; R28; R31; 710; Urban environment; Hedonic pricing method; Marginal willingness to pay; Implicit price; Environmental amenities